PENGARUH PERGANTIAN MANAJEMEN, OPINI AUDIT, UKURAN PERUSAHAAN, DAN PROFITABILITAS PERUSAHAAN TERHADAP AUDITOR SWITCHING - Farhan Ilhamsyah (2020)
This research was conducted to find empirical evidence regarding the effect of change in management, audit opinion, company size, and company profitability on auditor switching. The determination of the sample in this study used a purposive sampling method so there were 80 observations consisting of 20 companies listed on the Indonesia Stock Exchange in 2015-2018. This study uses logistic regression analysis with the SPSS program. The test results state that change in management affect auditor switching. Whereas audit opinion, company size, and company profitability do not affect auditor switching. Keywords : change in management, audit opinion, company size, company profitability, auditor switching.